Prevalence of death due to Firearm (Gunshot) injuries in Forensic Cases, in Kabul city, Afghanistan - Nijrabi, Hasibullah Baha; Ahmadi, Mohammad Sadeq; Salih, Mohibullah (Technium Social Sciences Journal, 2022)
Introduction: firearms (rifles, pistols, grenades, mines, and suicide bombers) cause gunshot injuries. In addition to destructive damage, the use of these weapons causes severe health damage, including bed sentences, disability, and death, which impose a heavy burden on the health sector and society with many adverse consequences for the social system. Objective: to assess the prevalence of deaths due to firearm injuries in the cases brought to the Kabul Forensic Medicine Center. Methods and Materials: This is a descriptive cross-sectional study. We have collected the data in a census manner from March 21, 2019, to March 19, 2020. We have retrieved the demographic information from the database of Kabul Forensic Medicine Center and analyzed it using SPSS version 26. Results: we went through the files and reviewed the demographic information of 1538 dead bodies which were brought to the Kabul Forensic Medicine Center, from March 21, 2019, to March 19, 2020, of which 466 (30.29%) were due to firearm injuries. Among those victims, 428 cases (91, 84%), were men, and 28 cases (8.16%) were female. The youngest age of the victims was 18 years and the oldest age of the victims was 40 years. The most common site of injury was the head (34.97%), and the most common cause of death was the destruction of brain tissue and severe internal and external bleeding (34.97%). The distance of gunshot was distant in most of the cases (52.78%). In most of the cases (69.74%), the type of wound canal originated with the exit wound. Conclusion: the death prevalence due to firearm injuries was 30.29%. Male, in the second, third, and fourth decades of life were victims in the majority of cases. In terms of anatomical location, the causes of death in most cases were firearm injuries to the head, destruction of brain tissues, and severe internal and external bleeding.